Shared automated vehicles: Review of business models - Adam Stocker; Susan Shaheen (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2017)
This paper provides an introduction to the current state of vehicle automation and shared mobility. The paper discusses current shared mobility business models to foster a better understanding of these systems at present and to set the stage for possible future shared automated vehicle (SAV) business models. The discussion covers current SAV pilot projects around the world and then explores potential SAV business and service models considering high or full automation (Level 4 and higher). The paper ends with a discussion of the literature regarding projected SAV impacts. Although the future of SAVs is uncertain, this briefing paper begins the dialogue around SAV business models that may develop, which are informed by current shared mobility services.
Keywords: 330; Kraftfahrzeug; Drohne; Mensch-Maschine-System; Autovermietung; Geschäftsmodell